THE USE OF CASE-STUDY TECHNOLOGY IN THE FORMATION OF STUDENTS' KNOWLEDGE OF COMPUTER HARDWARE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
One of the main tasks of modern education is to discuss the role and effectiveness of the use of new innovative technologies for the effective organization of education.The purpose of this article is to develop students' critical thinking and independent work skills through the use of interactive methods in the study of computer hardware in higher education. materials are given.